Vision screening of school children in greenland 2017-2022: coverage and low vision prevalence - Nick Duelund; Ivan Nisted; Ivalu Frederiksen; Marit Eika Jørgensen; Steffen Heegaard; Hanne Jensen (International Journal of Circumpolar Health)
Vision screening during childhood is vital for the early detection and treatment of visual impairment that may significantly impact a child’s development and quality of life. This nationwide cross-sectional study used data from Greenland’s national electronic medical records, including 2,493 six-year-old children from July 2017 to July 2023, to evaluate the coverage rate of vision screening and the prevalence of low vision in Greenlandic schoolchildren. The participation rate in vision screening increased from 43% in 2017 to 61% in 2022, while referral rates to ophthalmologists decreased from 14% to 5%, despite a consistent prevalence of low vision. The mean prevalence of impaired vision (0.3 logMAR / ≤0.50 Snellen decimal) in the better-seeing eye at the vision screening throughout the study period was 3%. At the same time, it was 8% for the worse-seeing eyes, indicating a continuous need for ophthalmological evaluation of the Greenlandic children. This study highlights healthcare delivery challenges in Greenland’s sparsely populated areas and emphasises the need for new national guidelines to optimise referral processes. Utilising other healthcare professionals, such as optometrists, for vision screenings and ensuring follow-ups are critical for improving the visual health outcomes of Greenlandic children.